2018 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--30869
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Importance of Leadership in their Future Careers Relative to Other Foundational, Technical and Professional Skills among Senior Civil Engineering Students

Abstract: Many demands are placed on undergraduate students to possess a broad range of foundational, technical, and professional knowledge and skills when they graduate. Expectancy value theory (EVT) indicates that students will be more motivated to learn topics that they believe will be important in their future, due to utility value. Self-efficacy beliefs also contribute to learning. Given this framework, the research explored student perceptions about the importance of leadership to their future professional careers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Sadly, very rarely do the DTS apprentices mention leadership and people management skills as being a desirable attribute in the view of employers when they make recruitment decisions. Research by Bielefeldt (2018) broadly supported my own findings: learners in technical subjects generally have a poor appreciation of the value of interdisciplinary skills. Bielefeldt's research showed that just a little over one in four (28 per cent) civil engineering students include leadership in the top five most important influencing factors in their professional success in the future, although this was higher than had previously been measured some five or so years earlier.…”
Section: The Challenges Of Engaging Technically-focused Apprentices I...supporting
confidence: 61%
“…Sadly, very rarely do the DTS apprentices mention leadership and people management skills as being a desirable attribute in the view of employers when they make recruitment decisions. Research by Bielefeldt (2018) broadly supported my own findings: learners in technical subjects generally have a poor appreciation of the value of interdisciplinary skills. Bielefeldt's research showed that just a little over one in four (28 per cent) civil engineering students include leadership in the top five most important influencing factors in their professional success in the future, although this was higher than had previously been measured some five or so years earlier.…”
Section: The Challenges Of Engaging Technically-focused Apprentices I...supporting
confidence: 61%
“…A study by Fernando, Amaratunga and Haigh [37] indicated that there were variances in women's capability, personality, and career aspirations, and the one-size-fits-all support program may be ineffective. Many other studies also highlighted the need to consider the unique circumstances, strengths, and areas for the development of each individual and provide personalized support for women's career development [31,43,44]. In fact, while a few companies in this study did provide more personalized support, such as career coaching, individual mentoring, and advice on flexible working arrangements, many companies lacked this kind of tailored support.…”
Section: Theme 1: Promoting Career Developmentmentioning
confidence: 89%
“…Data from this same study indicated the most desired leadership-enabling competencies in graduating engineering students were: communication skills, professionalism, critical thinking/problem-solving, self-awareness, ambition/drive, time management, management, ethics/responsibility, big-picture thinking, humility, teamwork/collaboration/networking, quality control, adaptability, computer skills, safety/risk management, assertiveness, people focus, legal knowledge, and economic principles and trends [5]. While leadership-enabling competencies may vary by discipline, there is a pressing need across all engineering industries for more graduating engineers to be prepared with strong inter-and intrapersonal skills when entering the workforce in addition to their industryspecific technical knowledge [4], [14], [15].…”
Section: Leadership In Engineeringmentioning
confidence: 99%